OCCURRENCE OF SHRINKFLATION IN THE POLISH FOOD MARKET FROM THE PERSPECTIVE OF CONSUMERS - Justyna Obrębska; Agata Malak-Rawlikowska (Annals of the Polish Association of Agricultural and Agribusiness Economists)
. The aim of the study was to identify the occurrence of shrinkflation in the Polish food market and its perception by consumers. Data collected from 300 consumers using a diagnostic survey method were subjected to simple statistical analysis. It was confirmed that especially during periods of high inflation, during crises, producers reduced product packaging, while maintaining the price at the same or higher level. The results of consumer preference studies indicated similar observations to those presented in foreign literature. It was noted that this phenomenon is most often noticeable in the case of sweets, juices and non-alcoholic beverages, as well as dairy products. When shopping for food, respondents pay more attention to the price of products, which means that they notice an increase in the price of food goods more quickly than a reduction in weight. The impact of reducing the packaging of food products on further consumer decisions about their purchase depends on many factors, such as: their price, the price of substitutes and the type of a given good. However, regardless of place of residence and gender, respondents prefer that producers increase the price of goods without reducing their weight. In order not to mislead consumers, it is recommended that actions described as shrinkflation be accompanied by clear labeling of the product that has been shrunk.